PENGOLAHAN LARUTAN DETERJEN DENGAN BIOFILTER TANAMAN KANGKUNGAN (IPOMOEA CRASSICAULIS) DALAM SISTEM BATCH (CURAH) TERAERASI - Dwi Adhi Suastuti, Ni G. A. M; Suarsa, I Wayan; Kurnia Putra R, Dwi (Jurnal Kimia (Journal of Chemistry), 2015)
This study was aimed to determine the ability of kangkungan plant (Ipomoea crassicaulis) as a biofilter in the treatment process of detergent solution with the use of an aerated batch system (bulk). The processing units were conditioned in a Styrofoam container equipped with an aeration system. A total of 24 L detergent solution and 5 kangkungan plants were applied in the units. As a comparison, a control unit containing the same solution without the addition of kangkungan plants was also carried out. Investigations of the ability of kangkungan in reducing the content of the pollutants which were measured as COD value, surfactant and phosphate levels were run within 30 days of observations. After 30 days it was found that there was a decrease in surfactant and phosphate levels, which were 97.76%; and 90.77%, respectively while the control showed a decrease of 50.79% and 51.53%, respectively
Keywords: Biofilter, Ipomoea crassicaulis, surfactant, phosphate, detergent solution